Complete Pathological Response After Neoadjuvant Chemo-Immunotherapy in Malignant Pleural Mesothelioma - Tostes, Francinne T.; Zugman, Miguel; Paes, Vitor R.; Schvartsman, Gustavo (Frontiers in Oncology, 2022)
Malignant pleural mesothelioma (MPM) is a poor prognosis disease, patients who are deemed eligible for resection usually are submitted to a multimodal therapy treatment that involves neoadjuvant chemotherapy followed by extrapleural pneumectomy/pleural decortication and radiotherapy with a median overall survival of 13 to 23.9 months. In the first-line setting, no major improvement was achieved in the last 20 years since the combination of cisplatin and pemetrexed was established as standard of care. Immune checkpoint inhibitors have been studied in the refractory setting and incorporated as treatment options regardless of PD-L1 status. Herein, we report the first case of our knowledge of a borderline-resectable epithelioid pleural mesothelioma who underwent neoadjuvant therapy with cisplatin, pemetrexed and off-label pembrolizumab who was able to be operated, and obtained a complete pathological response (pCR) with sustained benefit, currently disease and treatment-free 14 months after surgery, suggesting a possible new horizon for these patients.